Properties of boiled or steamed Procambarus clarkii girard and Procambarus zonangulus crawfish tail meat during refrigerated and frozen storage - Shackelford, John B; McMillin, Kenneth W; Bankston, J David; Janes, Marlene E; Lampila, Lucina E (Agriculture and Food Sciences Research, 2024)
This research was conducted to address the different cooking methods of crawfish processors and determine the refrigerated or frozen shelf-life of cooked product. Live crawfish, (Procambarus clarkii girard and Procambarus zonangulus), were either boiled or steamed before storage of 11 days in refrigerated (3°C) conditions or six months in frozen storage (-18°C). There were minimal moisture, ash, protein, and fat differences with cooking type or storage type. There were no E.coli/coliforms in samples and aerobic plate counts were less than 3 log10 colony forming untis (CFU)/g after 6 mo frozen storage and higher than 3 log10 CFU/g after 3 days of refrigerated storage. Lipid oxidation by TBARS increased, but was less than 0.53 mg MDA/kg during storage. Peak force, total shear work, pH, L*, a*, b* color values were variable during storage, but not different between cooking treatments at each storage period. Mineral and fatty acid analyses were similarly variable. There were no differences between boiling and cooking crawfish for most variables and natural variation among the samples might explain variability in refrigerated and frozen storage. Processors can use either boiling or steaming to cook crawfish and store cooked crawfish for 3 days in refrigerated storage and for 6 weeks in frozen storage with minimal changes in properties.